Synthesis and Spectral Properties of 1-(2’Methoxybenzyl)-2-(2’-Methoxyphenyl)-Benzimidazole Complexes with Cu(II), Co(II), Mn(II), U(VI) and Ce(IV) - Vijayan, K.; Prabhakar, L.D.; Uma, M.; Umarani, C. (Asian Journal of Chemistry, 2010)
A series of square planar complexes, copper(II) and interesting binuclear octahedral low spin complexes of cobalt(II), manganese(II) with corresponding anion bridges and octahedral complexes of cerium(IV) sulfate and polynuclear complexes of uranium(VI) phosphate of 1-(2´-methoxybenzyl)-2-(2´-methoxyphenyl)–benzimidazole were synthesized and studied by spectral, magnetic, thermal and conductance studies. The copper(II) complexes were assumed to be square planar complexes since a significant absorption band was detected in the range below 17,000 cm–1. A strong IR band appearing around 1,490 cm–1 was assigned to the C=N stretching mode, and it is observed that this band was shifted to lower frequencies upon coordination. The measured magnetic moments support square planar copper(II) and low spin ocatahedral cobalt(II), manganese(II) geometry. As expected the uranium(VI) and Ce(IV) complexes yield diamagnetic susceptibilities. Conductance studies show the existence of both ionic and non-ionic species present in all cases.